Interpretation of in-situ tests in clay with particular reference to reclaimed sites - Cao, Laifa (2009)
The undrained expansion and subsequent contraction of both spherical and cylindrical cavities in a modified Cam clay (MCC) material are analysed. The governing equations are formulated in an exact marmer and subsequently solved using a simple numerical integration. A simplified close-form solution has also been obtained for the limit cavity stress. The solution is applied to the interpretation of the piezocone (CPTU) test and for the prediction of the overconsolidation ratio (OCR), the undrained shear strength (su) and the rigidity index. Results indicate the validity of the solution when the effect of strain rate and the initial stress state are considered. The cavity expansion solution is also used for the interpretation of the lift-off pressure in the dilatometer test (DMT) and for the prediction of OCR. Reasonable predictions of OCR are observed when results are compared with a large collection of oedometer test data in the Singapore marine clay.